A televisão pública brasileira na contemporaneidade : o caso da TVU da UFMT - Bezerra, Nilo Alves (2012)
Technological advancement has brought new tools for mass communication. The digital image, the Internet and mobile devices have changed the way people communicate. Television, which revolutionized the world in the last century is losing its hegemony, but is still the larger scale of operation. The communications professional television must conform to the new form of audiovisual, more interactive and multiprogramming. The profusion of new television stations also changes the mass culture, now more targeted. This research is an analysis of how public TV, specifically the TV UNIVERSITY UFMT, facing this new situation, by checking that the major problems and new possibilities to fulfill their role in contemporary society.